Combined stiffness characteristic of metal rubber material under vibration loads. (September 2019) - Fu, Hailong; Hua, Zhengli; Zou, Longqing; Wang, Yue; Ye, Jianbin
Metal rubber is one kind of elastic cellular metal material, which is widely used in vibration isolation environment for its excellent properties of elasticity, energy dissipation, and environmental adaptability. However, the stiffness range of one single metal rubber is restricted, which limits its ability of vibration isolation, especially under the complex vibration loads. In this paper, a method of spatial overlay combination is presented to widen the range of the stiffness of metal rubber material. The contact behavior of the metal spiral rolls and the influence factors of manufacture to the stiffness are investigated according to the micro-spring theory and the energy dissipation theory. The static tests under cycling loading are conducted to obtain the average stiffness and the equivalent stiffness of the combined metal rubber. After the comparisons, the combined metal rubber has a better stiffness range than the individual element. The diameter of metal wire and the relative density of metal rubber are two important influence factors to the combined stiffness, which are verified by the experimental tests and finite element simulation.